Реки: повесть / Евгений Гришковец - Гришковец Евгений Валерьевич (Махаон, 2008)
Экземпляры: ф.15 (20190419) / Инвентарный номер: 59503 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 85 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44